2017
DOI: 10.1016/j.ympev.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyte-forming cyanobacteria from Brazilian saline-alkaline lakes

Abstract: Studies investigating the diversity of cyanobacteria from tropical environments are scarce, especially those devoted to the isolation and molecular characterization of the isolated strains. Among the Brazilian biomes, Pantanal has mainly been examined through microscopic observation of environmental samples, resulting in lists of morphotypes without any genetic information. Recently, two studies were conducted evaluating the morphologic and genetic diversity of cultured non-heterocytous cyanobacteria in this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 55 publications
4
23
0
Order By: Relevance
“…Morphological evaluations have shown that the cyanobacterial strain CENA543 belong to the genera Nostoc (Genuário et al, 2017 ). In a phylogenetic tree based on 16S rRNA (Figure 9 ), Nostoc sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological evaluations have shown that the cyanobacterial strain CENA543 belong to the genera Nostoc (Genuário et al, 2017 ). In a phylogenetic tree based on 16S rRNA (Figure 9 ), Nostoc sp.…”
Section: Discussionmentioning
confidence: 99%
“…The cyanobacterial strains studied were isolated from water samples that had been collected from several saline-alkaline lakes located at Centenário farm in the southern part of the sub-region Nhecolândia in the north of the municipality of Aquidauana, Mato Grosso do Sul State, Brazil (Andreote et al, 2014 ; Genuário et al, 2017 ; Figure S1 ). The Nostoc sp.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the most extreme cyanobacterial blooms are found during the driest period (August to November), with the highest alkalinity, EC and temperature values (Santos et al, 2011). Two major bloom-forming cyanobacterium have been identified (Andreote et al, 2014;Costa et al, 2016;Genuário et al, 2017;Vaz et al, 2015), Anabaenopsis elenikinii and Arthrospira platensis, primary producer (halo)alkaliphilic oxygenic cyanobacteria (Sorokin et al, 2015) that fix inorganic carbon and produce oxygen. These blooms occur during the 5 dry season and disappear in a few hours after the first heavy rains of the wet season.…”
Section: Studied Areamentioning
confidence: 99%
“…The genus Aliinostoc, the members of which showed morphological characters similar to members of the true Nostoc, was described by Bagchi et al [4] on the basis of its distant phylogenetic positioning from Nostoc sensu stricto. At present, majority of the strains of the genus Aliinostoc have been reported from tropical regions, except strains PCC 8122 and PCC 8976 that were reported from USA and France respectively [10][11][12]. The members of the genus Aliinostoc are usually found in habitats that are rich in dissolved salts and ions.…”
Section: Introductionmentioning
confidence: 99%